Relationship between the inflammatory index in the diet and breast cancer (Research, Society and Development, 2021)
This research aims to bring together studies that show the relationship between the inflammatory index of the diet (IBD) and the incidence of breast cancer (CM). This is an integrative literature review. The selection of studies was carried out during the months of July and August 2021, in the databases: LILACS, PUBMED and SCIENCE DIRECT via Capes Periodical portal. Initially, the strategy for the search for studies was composed of a combination of controlled descriptors (Index; Inflammation; Diet; Breast cancer). The combination of descriptors was performed using the Boolean operator AND. After the search and selection process using the criteria mentioned in the methodology, 5 articles were selected. A strong and independent association between the DII score and the incidence of MC was observed in the results of the selected studies, in which a diet with a high DII score was correlated with an increased risk of the incidence of MC and the opposite was also observed. Future studies are needed to obtain information on the relationship between diet-associated inflammation and the risk of MC. These findings deepen the understanding of the role of diet in breast carcinogenesis.